E-SERVQUAL EFFECT ON BRAND IMAGE THROUGH E-SATISFACTION IN INDONESIAN AIRPORTS APPS USERS AT SOEKARNO-HATTA AIRPORT - Aziz, Aghni Aulia; Aliman, Aliman (Jurnal Review Pendidikan dan Pengajaran, 2024)
The development of the internet has caused changes in the world of transportation where the digitalization system makes it easier for consumers to make ticket reservations, view flight schedules, and others. The more consumers can influence the quality of electronic services, it is necessary to pay attention to the quality of electronic services that can affect the brand image of users of the quality of electronic services in the Airport Apps Indonesia application. This study focuses on the effect of e-service quality on brand image through e-satisfaction on the Indonesia Airport Apps application at Soekarno-Hatta Airport. The purpose of this study was to determine the effect of e-service quality on brand image through e-satisfaction on the Indonesia Airport Apps application at Soekarno-Hatta Airport. The research methodology uses quantitative methods with data obtained from the Indonesian Airport Application user questionnaire which opens 260 samples and the analysis technique used is Partial Least Square with processing using Smartpls v3.3.3 software. Hypothesis testing with t-test statistics. The results showed that the effect of e-service quality had an effect on e-satisfaction, then e-satisfaction had an effect on brand image, then e-service quality had an effect on brand image, and e-service quality had an effect on brand image through e-satisfaction.